Transfer of Odor Perception From the Retronasal to the Orthonasal Pathway - He, Rui (Chem Senses, 2020)
Although orthonasal odorants are often associated with the external environment, retronasal odorants are accompanied by consummatory behaviors and indicate an internal state of an animal. Our study aimed to examine whether the same odorants may generate a consistent perceptual experience when 2 olfactory routes potentiate variations in concentration in the nasal cavity and orosensory activation. A customized lick spout with vacuum removing odorants around the animal’s nares was used to render a pure retronasal exposure experience. We found that pre-exposing rats to odorants retronasally with positive or negative reinforcers (sweet or bitter) lead to a significant learning rate difference between high- and low-vapor-pressure odorants. This effect was not observed for novel odorants, suggesting that odorants may generate similar perceptual quality in a volatility-dependent manner.